Impact of nutrients and water level changes on submerged macrophytes along a temperature gradient: A pan-European mesocosm experiment - Ersoy, Zeynep; Scharfenberger, Ulrike; Baho, Didier L; Bucak, Tuba; Feldmann, Tõnu; Hejzlar, Josef; Levi, Eti E; Mahdy, Aldoushy; Nõges, Tiina; Papastergiadou, Eva; Stefanidis, Konstantinos; Šorf, Michal; et al. (Global change biology, 2020)
Submerged macrophytes are of key importance for the structure and functioning of shallow lakes and can be decisive for maintaining them in a clear water state. The ongoing climate change affects the macrophytes through changes in temperature and precipitation, causing variations in nutrient load, water level and light availability. To investigate how these factors jointly determine macrophyte dominance and growth, we conducted a highly standardized pan-European experiment involving the installation of mesocosms in lakes. The experimental design consisted of mesotrophic and eutrophic nutrient conditions at 1 m (shallow) and 2 m (deep) depth along a latitudinal temperature gradient with average water temperatures ranging from 14.9 to 23.9°C (Sweden to Greece) and a natural drop in water levels in the warmest countries (Greece and Turkey). We determined percent plant volume inhabited (PVI) of submerged macrophytes on a monthly basis for 5 months and dry weight at the end of the experiment. Over the temperature gradient, PVI was highest in the shallow mesotrophic mesocosms followed by intermediate levels in the shallow eutrophic and deep mesotrophic mesocosms, and lowest levels in the deep eutrophic mesocosms. We identified three pathways along which water temperature likely affected PVI, exhibiting (a) a direct positive effect if light was not limiting; (b) an indirect positive effect due to an evaporation-driven water level reduction, causing a nonlinear increase in mean available light; and (c) an indirect negative effect through algal growth and, thus, high light attenuation under eutrophic conditions. We conclude that high temperatures combined with a temperature-mediated water level decrease can counterbalance the negative effects of eutrophic conditions on macrophytes by enhancing the light availability. While a water level reduction can promote macrophyte dominance, an extreme reduction will likely decrease macrophyte biomass and, consequently, their capacity to function as a carbon store and food source.
Keywords: mesocosm; voda; Nutrients; Švédsko; Temperature; latitudinal gradient; živiny; Lakes; Water; nutrients; shallow lakes; Sweden; climate change; macrophytes; water temperature; teplota; water level; jezera